2017
DOI: 10.18414/ksz.2017.7-8.805
|View full text |Cite
|
Sign up to set email alerts
|

A nemzetközi diverzifikáció, az innováció és a teljesítmény kapcsolata az európai élelmiszer-kiskereskedelemben

Abstract: Közgazdasági szemle , lX iV. éVf., 2017. július-augusztus (805-822. o.) agárdi irma-BerezVai zomBor-alt móniKa-anetta a nemzetközi diverzifikáció, az innováció és a teljesítmény kapcsolata az európai élelmiszer-kiskereskedelemben Kutatásunk során azt vizsgáltuk, hogy miként hat a nemzetközi diverzifikáció a nagy európai élelmiszer-kiskereskedelmi vállalatok piaci teljesítményére és innovációs tevékenységére. A világ 250 legnagyobb kiskereskedőjét tartalmazó toplista alapján az európai kiskereskedelmi vállal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The extent of globalization is also illustrated by statistical data; for example, German and French trading companies produce nearly 40 percent of their sales on foreign markets (Deloitte, 2016). The international retailers have been looking for new market opportunities as a result of the saturation of the internal markets, and in many cases, to enter the markets of developing countries have required less effort (Ag ardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of globalization is also illustrated by statistical data; for example, German and French trading companies produce nearly 40 percent of their sales on foreign markets (Deloitte, 2016). The international retailers have been looking for new market opportunities as a result of the saturation of the internal markets, and in many cases, to enter the markets of developing countries have required less effort (Ag ardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several researchers have studied the impact of participation in international markets on business performance. Researchers found out that expansion in the region, in the case of geographically and culturally closed countries, has a positive impact on business performance (the well-established business models do not require major changes in these counties), whereas markets require greater adaptations and higher cost levels in the case of farther and characteristically different countries (Agárdi et al , 2017; Hitt et al , 2006; Sohl, 2012; Oh et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Process innovation is often technological and digitalisation can also play a key role in the introduction of new channels, automation of warehousing, tracking, planning and control, and distribution management (Agárdi, Berezvai & Alt, 2017). Several EU SME competitiveness studies have shown that the digitalisation of firms has become a critical factor in their competitiveness and is expected to further increase its role in firm performance in the near future (Boikova, Zeverte-Rizva, Rivza & Rivza, 2021;Galindo-Martín, Castano-Martínez & Méndez-Picazo, 2023).…”
Section: The Innovation Aspect Of Competitivenessmentioning
confidence: 99%